THE RELATIONSHIP BETWEEN PARENTAL SOCIAL SUPPORT FOR AUTISTIC CHILDREN AND THE SOCIAL INTERACTION OF AUTISTIC CHILDERN IN SLB N SURAKARTA - Mutiara Hanuun Atsilah; Joko Yuwono; Sugini Sugini (Pusat Studi Difabilitas (PSD) LPPM Universitas Sebelas Maret, 2024)
This study aims to determine the correlations between parental social support for children with autism and the social interaction of children with autism at SLB N Surakarta. This research is a correlational quantitative study. The subjects of the research were 31 parents who have children aged 7-20 years. The sampling technique used was non-probability sampling with purposive sampling. Data collection technique using Likert scale instruments, consisting of a social support instrument and a social interaction instrument. The social support questionnaire used was a based on the theory of Wangi & Budisetyani (2020), which has 4 aspects and was developed into 40 statement items. The reliability test of the instrument used Cronbach’s Alpha, yielding a correlation coefficient of 0.837. The social interaction questionnaire based on the theory of Syahrial Syarbaini and Rudiyanta (as cited in Setyawan, 2016), which has 2 aspects and was developed into 40 statement items. The Cronbach’s Alpha reliability test on the social interaction instrument yielded a correlation coefficient of 0.905. The research results were analyzed using Pearson product-moment correlation test, yielding a calculated r-value of 0.618, with a significance level of p (0.000) < p (0.05), which means H0 is rejected and Ha is accepted. Therefore, it can be concluded that there is a strong correlation between parental social support for children with autism and the social interaction of children with autism.